Structural Basis of a Broadly Selective Acyltransferase from the Polyketide Synthase of Splenocin. Issue 20 (14th April 2018) - Li, Yuan; Zhang, Wan; Zhang, Hui; Tian, Wenya; Wu, Lian; Wang, Shuwen; Zheng, Mengmeng; Zhang, Jinru; Sun, Chenghai; Deng, Zixin; Sun, Yuhui; Qu, Xudong; et al.
Abstract: Polyketides are a large family of pharmaceutically important natural products, and the structural modification of their scaffolds is significant for drug development. Herein, we report high‐resolution X‐ray crystal structures of the broadly selective acyltransferase (AT) from the splenocin polyketide synthase (SpnD‐AT) in the apo form and in complex with benzylmalonyl and pentynylmalonyl extender unit mimics. These structures revealed the molecular basis for the stereoselectivity and substrate specificity of SpnD‐AT, and enabled the engineering of the industrially important Ery‐AT6 to broaden its substrate scope to include three new types of extender units. Abstract : Based on X‐ray crystal structures of the broadly selective acyltransferase (AT) from the splenocin polyketide synthase (SpnD‐AT) in the apo form and in complex with benzylmalonyl and pentynylmalonyl extender unit mimics, three residues were identified that play a critical role in determining the substrate specificity. Engineering of the corresponding sites in the canonical Ery‐AT6 led to significant changes in the substrate scope.